2008
DOI: 10.1242/jeb.012955
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulates aging and oxidative stress in Anopheles stephensi

Abstract: SUMMARYObservations from nematodes to mammals indicate that insulin/insulin-like growth factor signaling (IIS) regulates lifespan. As in other organisms, IIS is conserved in mosquitoes and signaling occurs in multiple tissues. During bloodfeeding, mosquitoes ingest human insulin. This simple observation suggested that exogenous insulin could mimic the endogenous hormonal control of aging in mosquitoes, providing a new model to examine this phenomenon at the organismal and cellular levels. To this end, female A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 53 publications
(63 reference statements)
7
90
0
Order By: Relevance
“…4C and SI Appendix, Fig. S25), similar to previous reports in the vector mosquito Anopheles stephensi (34). Furthermore, we found that oral administration of insulin did not alter feeding behavior or increase mortality compared with vehicle-fed flies within the time course of our assays (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4C and SI Appendix, Fig. S25), similar to previous reports in the vector mosquito Anopheles stephensi (34). Furthermore, we found that oral administration of insulin did not alter feeding behavior or increase mortality compared with vehicle-fed flies within the time course of our assays (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 89%
“…Because ERK signaling can be activated in the mosquito digestive tract by nutrients and insulin in the blood meal (30,34), we reasoned that the ERK pathway may couple signals in the meal with antiviral defense to protect insects from orally acquired viral infections, including arboviruses. To determine whether ERK activity in the gut impacts local viral susceptibility, we took advantage of U0126 to inhibit ERK signaling in the gut.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most vulnerable point of the malaria parasite life cycle is the transition from the human blood stream to the mosquito midgut. During this transition, hormones, growth factors and cytokines in infected blood can regulate aspects of mosquito physiology and lifespan that directly affect parasite development (Kang et al, 2008;Luckhart et al, 2003;Luckhart and Riehle, 2007;Pakpour et al, 2012;Surachetpong et al, 2009;Surachetpong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The blood meal is stored and digested in this organ, and it is the site of crucial phases in malaria parasite development in the mosquito host. Activation of midgut IIS can shorten mosquito lifespan and enhance susceptibility to P. falciparum infection in A. stephensi (Kang et al, 2008;Surachetpong et al, 2009). In particular, Pakpour et al (Pakpour et al, 2012) showed that insulin-induced susceptibility is due to the sustained activation of the phosphatidylinositol 3-kinase (PI3K)/Akt branch of the A. stephensi IIS, which in turn inhibits NF-κB-regulated immune gene expression.…”
Section: Introductionmentioning
confidence: 99%